Penambahan Fly Ash pada Komposit Polianilin/HCl/Fly Ash - Nila Rosana; Nugrahani Primary Putri (Universitas Negeri Surabaya, 2012)
In this study has been made composite between polyaniline as one of conductive polymers that has good conductivity by using fly ash as consequence getting a new material with a wider application. The aim of this research was to determine the effect of the addition of fly ash on the electrical properties of polyaniline/HCl/fly ash composite. The method of fabrication that we used to get synthesis of polyaniline was chemical oxidation while the composite of polyaniline/HCl/fly ash manufactured by using powder metallurgy, with a composition of 10%, 20%, 30% and 40% fly ash. The composite was tested using FTIR to find polyaniline functional groups, LCR meter (f = 50-106 Hz) to determine the electrical conductivity and dielectric constant of the composite, to find the content of fly ash was tested by using XRF, where as the morphology of the composite was tested by using SEM EDAX. Based on LCRs results, the electrical conductivity increased and dielectric constant decreased. The maximum electrical conductivity of the composite reached on the composition 20% fly ash was 3.86 Ã— 10-6 S/cm. The maximum dielectric constant at 20% fly ash composition reached 2.01 Ã— 104.